Co-editor - Tsaousi, Christiana (My University, 2026)
Co-Editor for the Special Issue "Digital Marketing Sustainability: Critical, Theoretical, and Practical Advances" in Sustainability (MDPI), an international peer-reviewed open access journal with an Impact Factor of 3.3 (2023) and CiteScore of 7.7. Responsibilities include managing manuscript submissions, coordinating peer review processes, and making editorial decisions on manuscript acceptance, revision, or rejection.